A Study on Structural Changes in Joints of Hand w.s.r. to Amavata (AYUSHDHARA, 2023)
Amavata is a chronic disease caused due to the vitiation of Vata associated with the Ama that circulates all over the body. Though various drug trails and treatment procedures were already carried out on Amavata, here an attempt is made to know the structural changes in the joints of hand that occurs in the disease, with the help of Radiography (X-ray), that may aid in the diagnosis and to know the efficacy of treatment. Objectives: To study the structural changes in joints of hand w.s.r. to Amavata. Materials and Methods: 30 diagnosed patients of Amavata were selected affecting the joints of hand (wrist, metacarpophalangeal and interphalangeal joints) and X-ray study was done to know the structural changes. Results: The study has shown the more of the structural changes in the form of soft tissue swelling, peri-articular osteopenia, bone erosion, joint space narrowing in the early stages of the disease, and secondary osteoarthritis, osteophytes, subluxation and ankylosis in the later stages. Conclusions: In metacarpophalangeal joint more of the structural changes are found in the form of soft tissue swelling, periarticular osteopenia and joint space narrowing. Bone erosion and osteophytes were lesser than the wrist joint and subchondral cyst, subluxation, secondary osteoarthritis and ankylosis were seen rarely and in the later stages of the disease. In interphalangeal joints soft tissue swelling, periarticular osteopenia, joint space narrowing was present as early changes. Subchondral cyst, subluxation, secondary osteoarthritis, bone erosion, osteophytes and ankylosis in the later stages of the disease.